Supraorbital and Auriculotemporal Nerve Entrapment: A Lesser-Known Cause of headache mimicking Migraine-like Symptoms - Rayamajhi, Anuj Jung; Bhattarai, Prajjwal Raj (Birat Journal of Health Sciences, 2023)
Extracranial headaches, although not rare, can be a significant contributor to chronic headaches, affecting approximately 4% of individuals. Among the potential causes of these headaches, entrapment neuropathy in the facial area is a prominent factor, with supraoptic nerve entrapment being a leading cause. The resulting pain typically manifests in the frontal forehead regions that are innervated by this nerve. Ultrasound-guided supraoptic nerve interventions serve a dual purpose, acting as both a diagnostic tool and a therapeutic measure, offering valuable benefits in managing this condition.